Exploring the Usefulness and Validity of Democratic Professionalism for Social Work Practice: A Cross-National Qualitative Case Study. (13th November 2021) - van der Tier, Michelle; Hermans, Koen; Potting, Marianne
Abstract: Democratic professionalism challenges social workers to see social institutions as potential fields for democratic action and to act as bridge agents between citizens and social institutions. Although scholars have identified democratic professionalism as a promising theory, the relevance of this approach has hardly been empirically explored and operationalised in social work practice. To address this gap, this article explores empirical examples of bridging practices in social welfare organisations and private shelter organisations in the Netherlands, Belgium and Germany. Data were gathered by means of a mixed method design (interviews N13, and focus groups N10). Based on our case analysis, we identify three types of practices that aim to close the gap between citizens and social institutions: task-sharing with citizens; raising public awareness about social issues and facilitating a public dialogue about social issues in close proximity to the lives of citizens. We found indications that the policy environment shapes both the relationship between social institutions and society, and social workers' actions and beliefs. Although we conclude that democratic professionalism is a promising theory for social work, more research is needed to further substantiate our findings and to explore the relevance of other aspects of democratic professionalism for social work practice. Abstract : In this article, we explore how social workers in the role of democratic professionals can bridge the gap between social institutions and citizens. Our cross-national case study data comprised interview and focus group sessions with social workers in social welfare organisations and private shelter organisations in the Netherlands, Belgium and Germany. We identified examples of this bridging dimension of democratic professionalism in the narratives of social workers about their encounters with citizens and their beliefs about the roles and responsibilities of both themselves and citizens. Based on our analysis, we identified three types of practices that exemplify how democratic professionals can bring citizens and social institutions closer together: (i) task-sharing practices, where democratic professionals and citizens share tasks that traditionally belong to the domain of the professional; (ii) raising public awareness about homelessness as a social issue and (iii) facilitating a public dialogue about social issues in close proximity to citizens' lives. We also found that the policy environment shapes how social workers act as democratic professionals and perceive their own professional role and responsibilities and those of citizens.